Gambaran Pelaksanaan Mobilisasi dengan Pola Eliminasi Fekal Pasien Paska Laparatomi : Overview of Mobilization Implementation with Fekal Elimination Pattern Post-Laparatomical Patients - Feki Surya Ardica; Leni Merdawati; Emil Huriani (Fakultas Keperawatan Universitas Andalas, 2013)
Patient post laparatomy just lay in bed and afraid to move because he felt pain in the scar. Constipation rate increased by 17-15% in patients who experience physical decline because long bed rest due to surgery. Recommended 6-10 hours post-op patients should be mobilized to accelerate the recovery of organs in patients. This research determine the effect of mobilization to fecal elimination patterns in patients after laparotomy in Irna B (Surgery) RSUP Dr. M. Djamil Padang. Pre-exsperiment Research design uses post-test only design with many use 13 respondents, sampling was done in quota sampling. Data collection techniques with observation. Analysis performed univariate. Results showed that there were 92% of respondents had normal fecal elimination patterns. Expected for the nursing, institution RSUP Dr. M. Djamil padang can be suggested that the mobilization is importan post-laparotomy patients to improve teh patient’s fecal elimination and revise SOP mobilization after surgery and socialized.